PROBLEMS AND THEIR SOLUTIONS OF TEACHING FOREIGN LANGUAGES AT A TECHNICAL UNIVERSITY - Nazarov, Rustam (Журнал иностранных языков и лингвистики, 2023)
This article will cover the main aspects of teaching English at a technical university. The purpose of this article is to eliminate the imbalance of classroom and individual work, taking into account the specifics of the technical university, to develop a methodology for the development of all language skills: speaking, listening, reading, grammar skills and expanding the vocabulary of students and the problems of teaching a foreign language on the example of a technical university and the search for ways to solve them, gives practical recommendations on teaching methods. The focus is on new technologies in teaching a foreign language.